(untitled) (Communications in Computational Physics, 2020)
Droplets on hydrophobic surfaces are ubiquitous in microfluidic applications and there exists a number of commonly used multicomponent and multiphase lattice Boltzmann schemes to study such systems. In this paper we focus on a popular implementation of a multicomponent model as introduced by Shan and Chen. Here, interactions between different components are implemented as repulsive forces whose strength is determined by model parameters. In this paper we present simulations of a droplet on a hydrophobic surface. We investigate the dependence of the contact angle on the simulation parameters and quantitatively compare different approaches to determine it. Results show that the method is capable of modelling the whole range of contact angles. We find that the a priori determination of the contact angle is depending on the simulation parameters with an uncertainty of 10% to 20%.